Aplikasi Asas Visual Untuk Kawalan Proses Statistik Dalam Perkilangan Perusahaan Kecil dan Sederhana (PKS) - Ali, Mohammad Kamarulzzaman; Ahmad @ Mohamad, Md Fauzi (Research in Management of Technology and Business, 2020)
Statistical process control (SPC) is one of the key quality control (QC) tools. However, the price of software is expensive and not suitable to the specific needs of each production process. In addition, production operators who have limited knowledge of SPC face difficulty to use commercial software. In this study, basic visual applications were developed specifically to meet the demands of industry to assist in the SPC implementation. The results show that the developed application is configured specifically for the process, this can allow operators to use SPC easily, even with limited SPC knowledge. By achieving consistent quality and performance, several advantages can be gained including scrap reduction, re-employment, and guarantee claims as well as being able to maximize company productivity. From this study shows that developed application is explicitly adapted to this method, it can enable the operator to implement SPC easily, even with minimal knowledge of SPC.